THE RELATIONSHIP BETWEEN FAST FOOD CONSUMPTION AND PRIMARY DYMENORHEA INCIDENCE IN ADOLESCENT GIRLS AT SMP IT AL-HIDAYAH, BEKASI DISTRICT - Pangaribuan, Maslan; Aritonang, Tetty Rina; Diah, Siti Amanah Tusa (NHM PRESS, 2023)
Introduction: Nowadays many teenagers like fast food (fast food). The negative impact of the habit of consuming fast food if consumed in excess can cause various health problems such as obesity, diabetes, hypertension, coronary heart disease, stroke, cancer, and so on (Pamelia, 2018). Research objective: To find out the relationship between consuming fast food and the incidence of primary dysmenorrhea in young women at SMP IT Al-Hidayah, Bekasi Regency in 2021. Research methods: Quantitative descriptive and correlation analysis with a cross-sectional approach. The population is all young women who have experienced menstruation at SMP IT Al-Hidayah Bekasi Regency in 2021 with a total sample of 45 respondents. The sampling technique is non-probability sampling using a purposive sampling approach. Univariate and bivariate data analysis used the chi square statistical test with a significance value of p.value = 0.05. The results of the study: Of the 45 young women who frequently consumed fast food 37 (82.2%), consumed bad fast food 37 (82.2%), and 39 (86.7%) experienced primary dysmenorrhea. Conclusion: There is a significant relationship between consuming fast food and the incidence of primary dysmenorrhea in young women at SMP IT Al-Hidayah, Bekasi Regency, in 2021 where p.value = 0.000.. Suggestion: It is hoped that young women can live healthily with a healthy diet and balanced nutrition.